Pharmacological treatment of oro‐facial pain – health technology assessment including a systematic review with network meta‐analysis. (29th July 2017) - Häggman‐Henrikson, B.; Alstergren, P.; Davidson, T.; Högestätt, E. D.; Östlund, P.; Tranæus, S.; Vitols, S.; List, T.
Summary: This health technology assessment evaluated the efficacy of pharmacological treatment in patients with oro‐facial pain. Randomised controlled trials were included if they reported pharmacological treatment in patients ≥18 years with chronic (≥3 months) oro‐facial pain. Patients were divided into subgroups: TMD‐muscle [temporomandibular disorders (TMD) mainly associated with myalgia]; TMD‐joint (TMD mainly associated with temporomandibular joint pain); and burning mouth syndrome (BMS). The primary outcome was pain intensity reduction after pharmacological treatment. The scientific quality of the evidence was rated according to GRADE. An electronic search in PubMed, Cochrane Library, and EMBASE from database inception to 1 March 2017 combined with a handsearch identified 1552 articles. After screening of abstracts, 178 articles were reviewed in full text and 57 studies met the inclusion criteria. After risk of bias assessment, 41 articles remained: 15 studies on 790 patients classified as TMD‐joint, nine on 375 patients classified as TMD‐muscle and 17 on 868 patients with BMS. Of these, eight studies on TMD‐muscle, and five on BMS were included in separate network meta‐analysis. The narrative synthesis suggests that NSAIDs as well as corticosteroid and hyaluronate injections are effective treatments for TMD‐joint pain. The network meta‐analysis showed that clonazepam and capsaicin reduced pain intensity in BMS, and the muscle relaxant cyclobenzaprine, for the TMD‐muscle group. In conclusion, based on a limited number of studies, evidence provided with network meta‐analysis showed that clonazepam and capsaicin are effective in treatment of BMS and that the muscle relaxant cyclobenzaprine has a positive treatment effect for TMD‐muscle pain.